STATUS ANAK AKIBAT PEMBATALAN NIKAH MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA DAN UNDANG-UNDANG NO. 1 TAHUN 1974 - Muhammad Nurcholis; Iswatun Hasanah (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2018)
Marriage in Islam is highly recommended to avoid immoral acts, but in the way that marriage can sometimes end up in the middle of the road because of the dispute or the court may decide that the marriage should end. The court can decide the marriage on grounds of annulment of marriage or divorce, due to the cancellation of marriage was considered a previous marriage never happens but when the wedding was canceled already have offspring status of children born of the marriage will be questioned, whether the child was a child legitimate or illegitimate children, concerning the status of the child as a result of an annulment in the Civil Code and law No. 1 In 1974 there was little difference, with their differences, the writers were interested to find out where the differences lie.